If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = -2(3x + -5) Reorder the terms: 28 = -2(-5 + 3x) 28 = (-5 * -2 + 3x * -2) 28 = (10 + -6x) Solving 28 = 10 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 28 + 6x = 10 + -6x + 6x Combine like terms: -6x + 6x = 0 28 + 6x = 10 + 0 28 + 6x = 10 Add '-28' to each side of the equation. 28 + -28 + 6x = 10 + -28 Combine like terms: 28 + -28 = 0 0 + 6x = 10 + -28 6x = 10 + -28 Combine like terms: 10 + -28 = -18 6x = -18 Divide each side by '6'. x = -3 Simplifying x = -3
| 70=7000/12*r | | 37+63= | | f(x+9)=x^2+2x+3 | | 4x^1/3-9x^1/3 | | 6x(3+4)=(6+3)+4 | | 3(12-x)=16-2 | | 15=4a | | p-2(3-2p)=2p+9 | | 3y-7x=28 | | x+(x+1.2)+(x-1.2)=28.5 | | (2x-4)*2=26 | | 75=5000/12*r | | p-18=59 | | 6a+18=6 | | 8.5+6*h/2=241.18 | | 99x+10=189 | | 1750-140= | | 3[(5x+3)-4]=4(2x-3) | | ln(x^2+3x)=2ln(2) | | 2a+18=6 | | 3[(5zx+3)-4]=4(2x-3) | | 5s-2+3(s-4)=5 | | .6c+11=2c+59 | | -6=-4(x+3)+2x | | -3(6p+2)-2(3-14p)=3(4+3p) | | 2(n+9)=5n | | -9/8t=7/10 | | -2p-(-10)+7p=-5 | | c+150=1750 | | -3b-4-3=5 | | 6y-10y-11=8y-2y+29 | | 0.9x-0.3(8-5x)=-0.4(x-8) |